Augmentation Mammoplasty With External Volume Expander–Assisted Autologous Fat Grafting in 305 Asian Patients. (19th February 2022) - Gao, Qiuni; Liu, Chengsheng; Qi, Zuoliang; Zhai, Peiming; Qi, Jun; Yang, Zhenyu; Hu, Yuling; Yuan, Xihang
Abstract: Background: External volume expander (EVE)-assisted autologous fat grafting is suitable for breast augmentation, but no large sample study in Asia has confirmed this method. Objectives: The authors reported their experience and outcomes in augmentation mammoplasty with EVE-assisted autologous fat grafting. Methods: A retrospective study was conducted in 305 female patients who underwent augmentation mammoplasty with EVE-assisted fat grafting between September 2012 and December 2020. Doctors utilized Crisalix (Crisalix S.A., Lausanne, Switzerland) for 3-dimensional (3D) imaging acquisition to measure the increase in breast volume to evaluate doctor satisfaction. The Preoperative Satisfaction with Breast and BREAST-Q questionnaires were employed to assess patients' preoperative and postoperative satisfaction, respectively. Results: The 305 female patients were aged 18 to 50 years (mean, 35.9 years). Among them, 68.52% were "very satisfied, " 18.69% were "somewhat satisfied, " 11.15% were "somewhat dissatisfied, " and 1.64% were "very dissatisfied" based on BREAST-Q analysis, whereas 100% were dissatisfied according to the Preoperative Satisfaction with Breast questionnaire. Doctors employed Crisalix to measure the increase in breast volume to evaluate doctor satisfaction. The results showed 76.01% had an increase in breast volume of 150 to 250 mL or >250 mL and were "satisfied" and "very satisfied, " respectively, 21.64% had an increase of 50 to 149 mL and were "somewhat satisfied, " and 2.30% had an increase <50 mL and were "dissatisfied." There were no complications, such as obvious fat liquefaction, infection, or fat embolism. Conclusions: Augmentation mammoplasty with EVE-assisted fat grafting is effective and satisfying in China. Crisalix for 3D imaging acquisition is convenient and effective in measuring breast volume. Level of Evidence: 4: